Sistemas de monitoreo activo para evitar ataques a servicios de red en el Hospital Dr. Napoleón Dávila Córdova - Cedeño, Ignacio (2023)
Active monitoring systems are the new trend in relation to cybersecurity, which are being used by private and public entities in order to provide a service that blocks network attacks and optimizes the work of recording information. The objective of this research is to analyze the application of an active monitoring system to prevent attacks on the network service at the Napoleón Dávila Córdova Hospital. The methodology consisted of the bibliographic analysis of several scientific articles in which the advantages of having this type of technology are presented, the questionnaire was designed for the interview with the head of the ICT area of the Hospital, and then the interview was conducted based on the questionnaire, then the analysis of the results of the interview was performed. The possible active monitoring tools that could be applied were searched for and evaluated. The security tools suitable for application in the network system, given that the characteristics of the active equipment are known, were Snort and Suricata, which can work together without any problem to detect intrusions and anomalies in the network.